2022
DOI: 10.1111/gcb.16196
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term exposure to heatwave‐like temperatures affects learning and memory in bumblebees

Abstract: Wild bees are responsible for pollinating more than 75% of plants globally and their pollination services are estimated to be worth several billions of dollars (IPBES, 2016;Potts et al., 2016). However, it is now widely accepted that wild bee species are declining across several continents (Dicks et al., 2021) and that these, as well as future declines, are a consequence of climate change Gérard et al., 2020;Soroye et al., 2020). Indeed, in a recent meta-analysis assessing the relative importance of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…We found clear evidence for temperature-mediated cognitive decline in associative learning performance, whereby wild pied babblers took more trials to learn the association between a colour cue and a food reward as maximum temperature during testing increased from 18°C to 42.3°C. This temperature-mediated decline in associative learning performance aligns with evidence from captive studies in mice [ 62 ], rats [ 63 ] and buff-tailed bumblebees [ 29 ], and recent evidence from wild Western Australian magpies [ 30 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We found clear evidence for temperature-mediated cognitive decline in associative learning performance, whereby wild pied babblers took more trials to learn the association between a colour cue and a food reward as maximum temperature during testing increased from 18°C to 42.3°C. This temperature-mediated decline in associative learning performance aligns with evidence from captive studies in mice [ 62 ], rats [ 63 ] and buff-tailed bumblebees [ 29 ], and recent evidence from wild Western Australian magpies [ 30 ].…”
Section: Discussionsupporting
confidence: 79%
“…detouring around a barrier instead of pecking it [ 28 ]. Similarly, buff-tailed bumblebees ( Bombus terrestris ) took longer to learn the association between a colour cue and a sucrose solution and forgot more quickly at 32°C compared to 25°C, suggesting workers in the wild may be less able to discriminate between flowers and remember the most rewarding ones during hot days [ 29 ]. However, most studies investigating heat impacts on cognition have tested animals in captivity [ 18 ]; the only study in wild animals found that Western Australian magpies ( Gymnhorina tibicen dorsalis ) were less likely to learn an association between a shape and a food reward when temperatures exceeded 32°C [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…R. Soc. B 291: 20240040 short-term exposure to high temperatures can impair both learning [24] and foraging [40] behaviours in bumble bees, although the underlying mechanisms remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This explanation goes along with our previous finding that Pristine impairs olfactory associative learning performance [45], which provides a basic measurement of a bee's ability to learn about relevant environmental stimuli, a necessary ability for successful homing. Likewise, short-term exposure to high temperatures can impair both learning [24] and foraging [40] behaviours in bumble bees, although the underlying mechanisms remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation